The Hibiscus bud weevil (Anthonomus testaceosquamosus Linell, Coleoptera: Curculionidae) - Alexandra M. Revynthi; Yisell Velazquez Hernandez; Juleysy Rodriguez; Paul E. Kendra; Daniel Carrillo; Catharine M. Mannion (EDIS)
A profile of the hibiscus bud weevil intended for the use of interested laypersons with some knowledge of biology as well as academic audiences. The hibiscus bud weevil, a pest of China rose hibiscus, originates from northeastern Mexico and southern Texas and can cause large economic losses to hibiscus growers. This fact sheet provides nursery owners, homeowners, and other interested people with information on this serious pest.